Amelioration of junctional epidermolysis bullosa due to exon skipping. (1st June 2016) - Kowalewski, C.; Bremer, J.; Gostynski, A.; Wertheim‐Tysarowska, K.; Wozniak, K.; Bal, J.; Jonkman, M.F.; Pasmooij, A.M.G.
Summary: Mutations in the COL17A1 gene lead to the genetic blistering disorder junctional epidermolysis bullosa generalized intermediate type (JEB‐gen‐intermed). Antisense oligonucleotide‐mediated exon skipping is a strategy that aims to skip the mutation‐containing exon and thereby produce a smaller but functional protein. COL17A1 is an interesting candidate, as 53 of the 55 exons (96%) can be skipped without disturbing the reading frame. Information on the functionality of the shortened protein product is important in order to obtain support for this therapeutic strategy. Here we report a patient with JEB‐gen‐intermed with amelioration of the phenotype due to exon 49 skipping by two distinct mechanisms – premature termination codon‐induced exon skipping and revertant mosaicism – both of which induced skipping of the same exon. The patient was compound heterozygous for two inherited COL17A1 mutations, a frameshift mutation in exon 18 (c.1490_1491delinsT, p.Ala497Valfs*23) and a nonsense mutation in exon 49 (c.3487G>T, p.Glu1163Ter). Upon clinical examination, skin patches were found that were resistant to blister formation. In these patches, naturally corrected cells were present that harboured an additional splice‐site mutation, c.3419–1G>T, resulting in skipping of the mutation‐containing exon 49. This natural gene therapy phenomenon shows that type XVII collagen with residues 1140–1169 deleted is largely functional. In addition, in affected skin cells a low level of exon 49 skipping was observed. Our results support the notion that skipping of a mutated in‐frame exon in COL17A1 ameliorates the phenotype.